An Enhanced 3DOF PID Control Scheme for Boost Converters with Improved Transient and Steady-State Performance - Abrar Abdul Hameed Rasheed; Marwan Kanaan Ismael; Ali Sachit Kaittan (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
This article discusses a novel Three-Degree-of-Freedom (3DOF) PID control design for DC-DC boost converters aimed at improving transient and steady-state performance. Boost converters are essential in power electronic devices but present challenges due to their nonlinear characteristics and right-half-plane zero issues that hinder traditional control methods. Basic PID controllers often exhibit faults like overshoot and poor disturbance rejection. The proposed 3DOF PID controller addresses these issues by incorporating set-point weighting and separating feedforward from feedback control, allowing for independent tuning of reference tracking and disturbance rejection. A systematic design approach is employed to optimize controller parameters for various operating conditions. The controller was implemented in a MATLAB/Simulink environment and tested against a detailed boost converter model. Simulation results show that the 3DOF PID controller significantly reduces rise time from 0.45 s to 0.18 s, settling time from 0.8 s to 0.3 s, and overshoot to under 2% compared to standard PID controllers, which typically show 10-12% overshoot. Additionally, under load disturbance, the voltage dip is reduced from 3 V to 1.2 V, with recovery time improved from 0.5 s to 0.2 s. Overall, the findings confirm that the 3DOF PID controller enhances transient response, disturbance rejection, and stability, making it a promising solution for high-performance power electronic applications. The acquired data confirm that the suggested 3DOF PID controller improves the boost converter's transient and steady state performance while preserving its stability in dynamic situations.